ENGLISH DEPARTMENT STUDENTS’ STRATEGIES IN ONLINE LEARNING DURING THE COVID-19 PANDEMIC - Hanafie, Dimas Aditya A; Korompot, Chairil Anwar; Tahir, Muh. (Universitas Negeri Makassar, 2022)
This research was a qualitative study using a case study approach. It aimed to find out: (1) the strategies used by the English department students in online learning; and (2) the students’ reasons for choosing the learning strategies in online learning. The instruments used were a questionnaire and an interview. A purposive sampling method was employed to select the participants, and 52 participants were chosen for this study. The results show that most students employ the same strategies for the environment-structuring aspect, as they always make sure that the conditions in which they are having an online lecture are conducive and comfortable enough to support their learning. From the result of the interview, the reasons the students use the strategies for each aspect are that (1) setting goals motivates students to learn and can be guidance in achieving good academic results; (2) a conducive learning environment supports online learning; (3) well-prepared students readiness in learning; (4) managing time is needed due to a lack of time in online classes; (5) seeking help to get a deeper understanding of the materials or instructions; and (6) evaluation helps to find out students lacks and needs in online learning.